PELATIHAN DAN PENERAPAN E-COMMERCE PEMASARAN PRODUK MIE KELOR DAN BELUT - Wahyuddin Wahyuddin; Usman Usman; Nurlinda Nurlinda (Mediasi: Jurnal Pengabdian Masyarakat, 2025)
The business sector is one of the sectors that plays an important role in the economy of the people of Parepare City. One of the rapidly growing business sectors in Parepare City is the culinary sector, including Kedai 'Aisyiyah. E-commerce is one of the technologies that can be utilized by MSMEs to develop their current businesses. The purpose of the proposed PKM is to increase sales turnover by implementing e-commerce in marketing moringa noodles and eels. The implementation of the activity is carried out in 3 (three) stages, including Activity Socialization, E-commerce Socialization and Education, and Application of e-commerce technology in selling noodles. Educational activities related to e-commerce were carried out at Kedai Aisyiyah on September 17, 2024, which was attended by the PKM Team of Muhammadiyah University of Parepare and the Manager of Kedai Aisyiyah as a partner delivered by a member of the PKM Team of Muhammadiyah University of Parepare (Wahyuddin). In his material, he conveyed the Definition and Concept of E-Commerce, Main Components of E-Commerce, Website or Platform, Online Payments and Digital Marketing. The training began by introducing the e-commerce feature developed by the PKM team with the website name https://kedaiaisyiyah.com/ . The conclusions are 1). Socialization and education about e-commerce are very important to improve the knowledge of Kedai 'Aisyiyah business managers. 2). E-commerce implementation training activities can improve the knowledge and skills of Kedai Aisyiyah managers in selling products using the e-commerce platform.